The role of financial stability considerations in monetary policy and the interaction with macroprudential policy in the euro area (European Central Bank (ECB), 2021)
Since the European Central Bank's (ECB's) 2003 strategy review, the importance of macro-financial amplification channels for monetary policy has increasingly gained recognition. This paper takes stock of this evolution and discusses the desirability of further incremental enhancements in the role of financial stability considerations in the ECB's monetary policy strategy. The paper starts with the premise that macroprudential policy, along with microprudential supervision, is the first line of defence against the build-up of financial imbalances. It also recognises that the pursuit of price stability through monetary policy, and of financial stability through macroprudential policy, are to a large extent complementary. Nevertheless, macroprudential policy may not be able to ensure financial stability independently of monetary policy, because of spillovers originating from the common transmission channels through which the two policies produce their effects. For example, a low interest rate environment can create incentives to engage in more risk-taking, or can adversely impact the profitability of financial intermediaries and hence their capacity to absorb shocks. The paper argues that the existence of such spillovers creates a conceptual case for monetary policy to take financial stability considerations into account. It then goes on to discuss what this conclusion might imply in practice for the ECB. One option would be to exploit the flexible length of the medium-term horizon over which price stability is to be achieved. Longer deviations from price stability could occasionally be tolerated, if they resulted in materially lower risks for financial stability and, ultimately, for future price stability. ...
More recent version: https://hdl.handle.net/10419/272969
Keywords: E3; E44; G01; G21; 330; Monetary policy; financial stability; macroprudential policy; financial frictions; systemic risk